The Effects of Referential Questions in the EFL Classroom - Martina Siposova (Communications - Scientific letters of the University of Zilina, 2007)
The article deals with complexity and importance of asking questions in the foreign language classroom. Since questions are one of the most essential teaching tools, teachers use them quite frequently during their lessons. The importance of referential questions, which are often referred to as “genuine or real” questions, lies in the fact that they have highly positive influence on the learning process. The qualitative study reported here shows that the impact of referential questions on university students can be characterised as constructive (i.e. effective and creative), leading to constructive conversation in the language seminars.